Northern Paraná under surveilance: searching and digitalization of photographs produced by the Paraná State Investigation Office of Social and Political Order (DOPS/PR) related with the North region (Revista de História Regional, 2008)
The present article aims to present some results of the PIBIC-CNPq (Scientific Initiation Institutional Program/National Council of Scientific and Technological Development) research Northern Paraná under surveillance: photograph mapping of DOPS/PR about Paraná northern region. That region, during the military dictatorship period was the stage of important events related to the contend of conflicting political projects, many times registered by the Paraná State Political and Social Order Division (DOPS/PR). The photograph singularity, as a historical document, was our main analysis source.